كاریگه‌ری سیستمی خوێندنی ئاوێته‌ له‌سه‌ر پرۆسه‌ی خوێندن له‌زانكۆدا / توێژینه‌وه‌یه‌كی مه‌یدانییه‌ ‌ له‌زانكۆی سلێمانی - ئه‌مین, تارا محمود سلێمان; رشید, شیرین ابراهیم محمد (Sulaimani Journal for Humanities, 2022)
The impact of blended learning on the study process at the university - A field study at the University of Sulaymaniy Blended learning is an educational system that most universities have resorted to during the outbreak of the Corona epidemic. Blended learning is a modern form of study in Iraqi society in general and in Kurdish society in particular. It was an appropriate solution to more than prevent the spread of the Corona epidemic and also to continue studying in universities. Despite that, this solution, which suited the teaching method, created many obstacles for students who had not previously practiced this type of study. Direct education between the student and the teacher has become another alternative, which distance education is using the electronic network of classrooms at the appropriate times. This educational circumstance created many problems for students who did not quickly adapt to this method of study. The current research aims to identify the impact of the integrated system on the learning process at the university from the point of view students, to identify the students' problems in this teaching system, and to identify the role of professors in this system from the point of view students. The research consists of two sides, the theoretical side and the field side, as the theoretical side consists of two chapters. The first chapter consists of the preamble to the research and defining concepts, while the second chapter contains a historical introduction and the most important foundations and needs of an integrated education system. As for the field side, it may be It consists of two chapters, as the third chapter contains the research methodology and field procedures, while the fourth chapter consists of presenting and analyzing information and presenting results and proposals for results and research proposals (100) male and female students in the Departments of the Faculty of Humanities. The questionnaire was relied on to obtain the field results. The questionnaire consisted of 24 questions directed to students to identify the impact of blended education on the study process at the university. Finally, the research reached a number of results and suggestions.